Research on PCK Theory Based on Core Literacy – A Case Study of High School Physics Teaching - Zhang, Yue (Journal of Theory and Practice of Contemporary Education, 2023)
The core quality of physics in senior high school aims to train students to understand nature from the perspective of physics, understand nature, learn to explore, experience scientific research methods and develop scientific thinking habits. Teachers should have certain means in the leading process. Therefore, under the premise of taking the core literacy of physics as the guidance, this paper, through the content of the basic core literacy of physics, once again studies the teacher's PCK theory of Schulmantift, analyzes the content of the PCK theory and its specific guiding role in teaching, summarizes the basic methods to achieve the core literacy of physics, and summarizes the construction process of the teacher's PCK theory. Eileen Chang was educated in Hong Kong from 1939 to 1941, and her writing mainly started after she dropped out of school. Therefore, Hong Kong can be regarded as the starting point of Eileen Chang’s literary creation. She mentioned Hong Kong many times in her works. It’s worth examining what characteristics Hong Kong has in Eileen Chang’s writing, and what significance the Hong Kong experience had for her life and writing. Sensory experiences were often paid attention to in the urban experience in Chang’s works, and the text was full of sound narration. However, relative to the content about vision, hearing has not been systematically valued. Therefore, from the perspective of sound, this article attempts to explore how Eileen Chang used hearing to rebuild her memory and explore the image of Hong Kong in her works.